2017
DOI: 10.1037/cpp0000213
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent and caregiver perspectives on provider–patient interactions in Type 2 diabetes.

Abstract: This study aimed to describe the experience of adolescents with Type 2 diabetes and their caregivers during medical encounters, in an effort to improve clinical care and outcomes in this population. Twenty-eight families were recruited from a Midwestern diabetes clinic. Adolescents (13-18 years old) identified as Black (50%), Caucasian (43%), and Hispanic (7%), with variable levels of glycemic control (glycosylated hemoglobin A1c ϭ 5.1-12.9%). Participants completed demographic and diseaserelated (adherence) q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Trust in the HCP is important and often facilitated by HCP assurances of confidentiality, honesty, good listening skills, and empathy (23). YAs with chronic illnesses also prefer direct communication with their HCPs rather than having HCPs communicate with their parents (24,25). These preferred characteristics mirror the elements of PCC characterized by trust, support, and patient engagement (26).…”
Section: During the Visit Verbal Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Trust in the HCP is important and often facilitated by HCP assurances of confidentiality, honesty, good listening skills, and empathy (23). YAs with chronic illnesses also prefer direct communication with their HCPs rather than having HCPs communicate with their parents (24,25). These preferred characteristics mirror the elements of PCC characterized by trust, support, and patient engagement (26).…”
Section: During the Visit Verbal Strategiesmentioning
confidence: 99%
“…Similarly, compared with non-Hispanic White youths with type 1 diabetes, caregivers of Hispanic youths with type 1 diabetes reported more problems with communication, getting diabetes information, and receiving care that takes into account the child and family circumstances (54). Additionally, one qualitative study of adolescents (13-18 years of age) with type 2 diabetes from racially/ethnically diverse backgrounds found that youths reported discomfort with health communication (e.g., feeling shy or having difficulties forming questions), as well as a preference among Black families for a Black doctor because of perceptions of receiving more effective care (25), which has been echoed in the adult literature (55).…”
Section: Cultural Considerationsmentioning
confidence: 99%
“…The authors outline ways in which pediatric psychologists can help provide support and improve delivery of care for these families. Amirniroumand et al (2017) and Simms, Baumann, and Monaghan (2017) each studied patient-provider interactions among adolescents and young adults with diabetes. Amirniroumand and colleagues gathered the perspectives of a racially diverse sample of adolescents (ages 13 to 18) with Type 2 diabetes and their caregivers regarding interactions with providers in an effort to understand processes within these interactions that may promote or undermine clinical outcomes.…”
Section: The Health Care Experience: Improving the Delivery Of Pediat...mentioning
confidence: 99%